Bentuk, Fungsi, dan Distribusi Reduplikasi Bahasa Arab pada Buku, Al-Anf Al-Ajīb karya Muhammad Attiyah Al-Ibrashi - Vandhim Aji Abimanyu; Darsita Suparno; Mauidlotun Nisa; Ahmad Hifni; Zacky Mubarak (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study aims to translate the Arabic children’s story Al-Anf Al-Ajib by Muḥammad Aṭiyyah Al-Ibrāshī and analyze its cultural adaptation compared to the well-known story of Pinocchio in Indonesia. Using a qualitative descriptive method with philological and intertextual approaches, the study reveals that Al-Anf Al-Ajib is a free adaptation of Pinocchio, modified to align with Arab cultural values. The changes include character names, settings, and moral focus, demonstrating the importance of cultural adaptation in children’s literature translation.